Hubungan Pengetahuan Ibu Akseptor KB Suntik Dengan Kepatuhan Kunjungan Ulang Di PMB Hj. Zuniawati Palembang Tahun 2023 - Wiwiet Wulandari; Vivi Oktari (STIKes Budi Mulia Sriwijaya, 2025)
Abstract Family Planning is an attempt to extend of plan the number and distance of a pregnancy by using contraception.The purpose of this research is to find out if there is any knowledge and attitude to the three-month use ofcontraceptives. The design of the research is analytic survey by using cross sectional approach. Sample whichtaken is all mothers who come to use the three-month contraceptives in Hj. Zuniawati Apprentice Palembangwhich amount 32 people. According to the univariate analysis result obtained that from 32 respondents, who usethe three-month contraceptives are 19 people (54,9%). According to the bivariate analysis result reachedmothers with good knowledge use a three-month contraception group of 17 people (27.0%) are more thanmothers with less knowledge who use a three-month contraception for 2 people (2.67%). According to bivariateanalysis result obtained that Mothers who have positive attitude use three-month contraception namely 16 people (25.7%) are much more than mothers who have negative attitude use three-month contraception for 3people (7.67%). From Bivariate analysis reached that there is a significant relation between knowledge with using three-month contraception (ρ value = 0,015), and reached that there‟s not a significant correlation between attitude with using three-month contraception (ρ value = 0,109), advice to health workers especially midwives who work in Hj. Zuniawati Apprentice Palembang 2022 to promote good counseling as to contraception, it is an effective and efficient contraception. Key Words: Knowledge, Attitude and Three-month Contraception Usage